n-Heptadecane-Impregnated Wood as a Potential Material for Energy-Saving Buildings - Can, Ahmet; Zigon, Jure (Mdpi, 2022)
Phase change materials (PCMs) are ideal for thermal management solutions in buildings. This is because they store and release thermal energy during melting and freezing. Spruce (Picea orientalis (L.) Peterm.) sapwood was impregnated with n-heptadecane (100%) as a PCM. The decay-resistance properties and thermal energy storage (TES) characteristics of the n-heptadecane-impregnated wood were studied. The phase change properties of n-heptadecane (nHD)-impregnated wood were characterized by Fourier-transform infrared (FTIR), thermogravimetry (TGA), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analyses. As confirmed by DSC analysis, nHD-impregnated wood demonstrated moderate performance in storing and releasing heat during the phase change process. Significant increases were observed in the 2800-3000 cm(-1) and 1471 cm(-1) peaks in FTIR spectra of wood samples impregnated with nHD, which showed C-H stretching in methyl and methylene groups and asymmetric deformation vibration of the paraffin methyl group (CH3-) and C-O stretch in lignin, respectively. It was observed that there was a change in the crystal structure of spruce wood samples after nHD impregnation. This study revealed that PCMs are resistant to wood-destroying fungi. The performance of nHD-impregnated spruce wood proves that it can be used as a thermal regulating building material to reduce energy consumption. In addition, it has been proven on a laboratory scale that the PCM used is highly resistant to biological attacks. However, large-scale pilot studies are still needed.
Keywords: n-heptadecane; phase change material; spruce wood; wood impregnation